2012
DOI: 10.2527/jas.2011-4049
|View full text |Cite
|
Sign up to set email alerts
|

Sow and litter response to supplemental dietary fat in lactation diets during high ambient temperatures1

Abstract: The objective of this experiment was to determine the impact of supplemental dietary fat on total lactation energy intake and sow and litter performance during high ambient temperatures (27 ± 3°C). Data were collected from 337 mixed-parity sows from July to September in a 2,600-sow commercial unit in Oklahoma. Diets were corn-soybean meal-based with 7.5% corn distillers dried grains with solubles and 6.0% wheat middlings and contained 3.24 g of standardized ileal digestible Lys/Mcal of ME. Animal-vegetable fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
18
3
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 33 publications
6
18
3
2
Order By: Relevance
“…In observations by Shurson and Irvin (1992), sows fed 10% corn oil increased back fat thickness by 1 mm during the lactation period. Previously, we observed a 7% increase (1.3 mm) in back fat for sows at weaning when they were fed a diet containing 6% A-V blend compared with sows fed no supplemental fat (Rosero et al, 2011). However, in the present study, we did not observe any differences among dietary treatments in loss of back fat.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…In observations by Shurson and Irvin (1992), sows fed 10% corn oil increased back fat thickness by 1 mm during the lactation period. Previously, we observed a 7% increase (1.3 mm) in back fat for sows at weaning when they were fed a diet containing 6% A-V blend compared with sows fed no supplemental fat (Rosero et al, 2011). However, in the present study, we did not observe any differences among dietary treatments in loss of back fat.…”
Section: Discussioncontrasting
confidence: 93%
“…This was above the evaporative critical temperature (22°C; Black et al, 1993); above this temperature, sows become heat stressed. As in our previous study (Rosero et al, 2011), we showed a linear increase in feed disappearance with increasing A-V blend in the diet. Schoenherr et al (1989) reported a greater feed disappearance for sows fed 10% supplemental CWG compared with sows fed no supplemental fat when sows were housed under heat stress conditions (32°C).…”
Section: Discussionsupporting
confidence: 89%
“…These data resemble our findings, in which parity 1 dams had loss of LEA over lactation with modest recovery during post-weaning. Contrary to our findings, Rosero et al (2012) indicated loss of loin muscle depth during lactation, as a measure of protein mobilization, was reduced as parity of dam increased. In the current study, we measured loin eye area at late gestation, weaning, and again post-weaning, not loin muscle depth.…”
Section: Discussioncontrasting
confidence: 86%
“…Firstly, these coefficients can be affected by the diet chemical composition and feed processing and secondly, animal factors such as body weight, genotype, sex, and physiological stage will also exert effects. 38 In the present study, we only used growing castrated males of the same age from the same genetic line, which had access to the same diet (feed composition and processing); so the only factor of variation between groups was the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, 21 -to 28-day-old pigs do not produce sufficient amounts of biliary salts to fully emulsify dietary lipids, whereas the pigs used in the present study would have had the capability to digest fats and oils up to an inclusion level of 6%. 38 In the present study vegetable oil was used as the fat source. This fat source has been reported to have a medium to high digestibility in swine 28 at 6.6% of the diet as-fed basis in the growing pig.…”
Section: Discussionmentioning
confidence: 99%